Gender bias in ACS management. (14th October 2021) - Murray, P; Blake, W M; Ward, D
Abstract: Background: Cardiovascular disease is implicated in approximately 1 in every 3 deaths occurring in both women and men worldwide. Numerically, it is responsible for more female than male deaths each year, due largely to longer life expectancy amongst women. Consequently, guidelines from the major international bodies recommend against the use of sex as a discriminating factor in the evaluation of chest pain. Still there remains a public perception of excess cardiovascular risk in men, contributing to a delay in the seeking of medical attention by women with symptoms of acute coronary syndrome (ACS). We hypothesise the attendant concern that unconscious gender bias amongst clinicians influences the management of patients presenting with ACS from triage to invasive assessment and treatment. Aim: To examine the relationship between patient gender and clinical management of ACS. Methods: We conducted a retrospective cross sectional study of all patients in whom ACS was suspected during a year long period using the laboratory database of a tertiary cardiac referral centre in Ireland. In all patients for whom high sensitivity cardiac troponin T assay was ordered during the full calendar year 2019, age, sex and troponin level were recorded. We determined the likelihood of invasive angiography for male versus female patients after adjustment for age and troponin result. Results: A total of 30, 560 requests for high sensitivity cardiac troponin T (troponin) were made to the laboratory in the year ending December 2019. Excluding 464 for technical and sampling issues, 30, 096 assays were included in the analysis. 43.84% (N=13, 194) of samples were female and 56.16% (N=16, 902) male. These samples were collected from 10, 807 patients (5, 294 female and 5, 513 male). Median age was 58 for females and 57 for males. The upper limit of normal in our institution for serum troponin is <14ng/L and there is no adjustment for sex. 22.01% (N=1, 165) of females and 33.39% (N=1, 841) of males had at least one troponin level reported above the normal range. Of female patients with at least one troponin above the normal limit, 10.21% (N=119) underwent invasive coronary angiography compared to 18.52% (N=341) of males. Of females in whom all troponin results were normal, 5.84% (N=241) proceeded to invasive angiography versus 9.18% (N=337) of males. Conclusion: Notwithstanding the limitations of lack of adjustment for risk profile, the results of this analysis demonstrate a higher rate of invasive angiography in males compared with females independently of troponin level. This is in keeping with previous research suggesting a gender gap in the approach of clinicians to ACS, and suggests an unconscious sex-based discrimination when making decisions around diagnosis and treatment. Education regarding the prevalence of coronary atherosclerosis, and interventions to alter the attitudes of clinicians, are some of the interventions suggested to close this gap. FUNDunding Acknowledgement: Type of funding sources: None.